Medicine shortages: Product life cycle phases and characteristics of medicines in short supply—A register study - Sarnola, Kati; Kari, Heini; Koskinen, Hanna (Frontiers in Pharmacology, 2022)
Introduction: Product life cycle refers to all phases of a product from development to active market phase and finally the phase in which products possibly exit the market. The product life cycle of medicines in short supply has not been studied in depth, although there is some indication of mature products and products with lower prices and profit margins being exposed to shortages more often. The aim of this study was to examine the product life cycle phases and characteristics of medicines in short supply as well as the features of medicine shortages in Finland from 2017 to 2019. Material and methods: Register data on medicine shortages of human medicinal products from 2017 to 2019 was combined with timely data on marketing authorizations and reimbursement status to gain data on product life cycle phases and characteristics (e.g., the age and the reimbursement status) of medicines in short supply and the features of medicine shortages. The data were analyzed in descriptive manner using appropriate statistical testing. Results: 3,526 shortages were reported during the 3-year study period and the number of shortages increased annually. The average duration of a shortage was 83 days and shortages affected 660 active pharmaceutical ingredients. Most often, shortages occurred with medicines affecting the nervous system, the cardiovascular system, and the genitourinary system. A majority of shortages (n = 2,689) was reported in the reimbursable medicines group, where shortages increased as the number of patients receiving reimbursements increased (p < 0.001). In the reimbursable medicines group, shortages most commonly involved medicines aged 15–19, 20–24, and 25–29, whereas with both reimbursable and non-reimbursable products the shortages most often occurred in medicines aged 50–54. The frequency of shortages differed between the groups (p < 0.001) when both age and reimbursement status were taken into account. Conclusion: Medicine shortages are common and affect commonly used medicines. Product life cycle phase has an effect on the frequency of shortages: Reimbursable medicines and medicines exposed to changes in life cycle are more likely to face a shortage. The impacts of product life cycle on the availability of medicines and medicine shortages should be studied in more detail.